Sustainable Vegetable Cultivation in the Nilgiris, Western Ghats through Valorization of Spent Mushroom Substrate - Annepu, Sudheer Kumar; P, Sundarambal; SM, Vanitha; AR, Suguna; S, Gurudevan; M, Sivalingam (Indian Horticulture, 2025)
The Nilgiris region, renowned for its cool climate and fertile soils, provides an optimal environment for cultivating temperate vegetables. Recent research highlights the potential of Spent Mushroom Substrate (SMS)—a by-product of mushroom cultivation—as a sustainable supplement to traditional organic manures like farmyard and poultry manure. Field trials conducted by the ICAR-Indian Institute of Soil and Water Conservation (ICAR-IISWC) at its Research Centre in Udhagamandalam, specifically in Basavakkal village, have demonstrated that recomposting SMS with rock phosphate can significantly enhance vegetable yields. Notably, crops such as carrots, beetroots, and broccoli exhibited yield increases ranging from 6% to 23% compared to conventional farming practices.Beyond yield improvements, the application of SMS has environmental benefits. Studies indicate that using SMS can reduce soil CO₂ emissions by approximately 26.5% compared to the use of traditional farmyard manure. This reduction contributes to a lower carbon footprint in agricultural practices. The integration of SMS into farming practices aligns with the principles of a circular economy, promoting the recycling and reuse of agricultural by-products. By repurposing SMS as a biofertilizer, farmers can enhance soil health, improve crop productivity, and adopt more sustainable and environmentally friendly agricultural methods. The utilization of Spent Mushroom Substrate offers a promising, eco-conscious alternative to traditional manures, fostering both agricultural productivity andenvironmental sustainability in the Nilgiris region.